FIRST LINE ANTI-RETRO VIRAL DRUGS DISRUPTS THE ESTRUS CYCLE OF WISTAR RATS - Ohihoin, Dr Aigbe Gregory (International Journal of Health Sciences, 2018)
Background: Patients with HIV AIDS are beginning to live longer and healthier lives due to the use of ARV therapy. The effect of long term usage of these agents on the reproductive potential of human females has not been well studied. The study of the estrus cycle in rats will give information on the possible effect of ARV's on the reproductive potential of humans. Aims: To elucidate the effects of the first-line ARV's, Efavirenz, Tenofovir and Lamivudine administered in a combined fashion, on the oestrous cycle of adult female Wistar rats. Material and Methods: Twenty-five female Wistar rats with a mean weight of 158.76g were used. A total of five groups of rats were involved in the study. Five rats were apportioned to each study group. All three ARV's were administered orally in a combined fashion to a particular group of Female Wistar rats and also administered individually to other groups while the control group received water. The estrous cycles of various groups of rats were monitored via microscopic analysis of their vaginal smears Results: The control group had a consistently regular cycle, while the cycles of the rats in the combination therapy group and the rats that received efavirenz alone, became elongated relative to the control group. There was a 48-hour enlongated proestrous phase some of the rats. Conclusions: First-line ARV's - Tenofovir, Efavirenz, and Lamivudine- disrupt the estrous cycle of adult rats. Further investigation of the long term usage of these drugs on the menstrual cycle of human females is therefore necessary